2020
DOI: 10.3389/fmicb.2020.01719
|View full text |Cite
|
Sign up to set email alerts
|

North American Propolis Extracts From Upstate New York Decrease Nosema ceranae (Microsporidia) Spore Levels in Honey Bees (Apis mellifera)

Abstract: Nosema ceranae infections in honey bees (Apis mellifera) pose a severe threat to colony health. Beekeepers have used dicyclohexylammonium fumagillin to control Nosema apis, although it may be ineffective against N. ceranae. We investigated the ability of various propolis extracts collected from Upstate New York (United States) to decrease in vivo N. ceranae infection levels when fed ad libitum to N. ceranae-infected honey bees. Propolis extracts, most notably a dichloromethane extract, significantly lowered sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Supplementation with proteins such as propolis and pollen was shown to prevent clinical signs of infection. Pollen supplementation increases the transcription of genes related to the expression of Vg and other important bioprocesses in infected bees [ 116 , 117 ], and administration of propolis extract decreases N. ceranae spore levels in honeybees [ 118 , 119 ]. Suwannapong et al (2018) observed a reduction in both mortality and infection rates after oral administration of propolis in Apis florea [ 120 ].…”
Section: Current Insights On Treatmentmentioning
confidence: 99%
“…Supplementation with proteins such as propolis and pollen was shown to prevent clinical signs of infection. Pollen supplementation increases the transcription of genes related to the expression of Vg and other important bioprocesses in infected bees [ 116 , 117 ], and administration of propolis extract decreases N. ceranae spore levels in honeybees [ 118 , 119 ]. Suwannapong et al (2018) observed a reduction in both mortality and infection rates after oral administration of propolis in Apis florea [ 120 ].…”
Section: Current Insights On Treatmentmentioning
confidence: 99%
“…In addition, this propolis extract treatment increased the trehalose levels and hypopharyngeal gland protein content in treated bees compared to an untreated control group ( Suwannapong et al, 2018 ). Dichloromethane extract of propolis from Upstate New York greatly reduced N. ceranae spore loads in a dose-dependent manner ( Burnham et al, 2020 ). A study in Italy that evaluated an ethanol extract of propolis from the honey bee A. mellifera demonstrated that treatment decreased the spore load of N. ceranae -infected worker bees ( Mura et al, 2020 ).…”
Section: Alternative Medicine For Treatment Of Microsporidiosismentioning
confidence: 99%
“…Many dietary supplements improve honey bee strength, immunity, and performance, thereby contributing to the maintenance of healthy colonies [8,15,19,[24][25][26][27][28]. Many studies investigated natural strategies against nosemosis, with plant and algal extracts as well as synthetic vitamin/mineral mixtures giving the best results [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]). These products, administrated to bees before or after the Nosema infection, significantly reduced mortality and infection rates [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%